Improvement of Processing and Marketing of Innovative Coconut and Nut-Based Products at the Sari Nadhi Business Study Group, Carangsari Village, Badung - Sudiarta, I Wayan; Semariyani , A. A. Made; Dewi, Ni Made Putri Pradnya Paramita; Rustini, Ni Made; Putri, Putu Ananda Icaka; Ni Luh Putu Putri, Setianingsih (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
The processing of agricultural products, especially coconuts into VCO, coconut oil, sounding, and tempeh, with several types of processed products for innovative snacks with soybean ingredients has been produced and marketed by partners in Carangsari Village and its surroundings, but with limited marketing, and the products still need to be improved in quality to be able to compete with similar products. The problems faced are that the product quality is inconsistent, the product packaging is still simple, and there is no knowledge of business management and bookkeeping, so there are obstacles in managing production and marketing. The solution to the problems faced is to improve processing technology and packaging technology; turnover increases; product quality and quantity increase Contribution to Sustainable Development Goals (SDGs):SDG 1: No PovertySDG 2: Zero HungerSDG 4: Quality EducationSDG 8: Decent Work and Economic GrowthSDG 9: Industry, Innovation, and InfrastructureSDG 17: Partnerships for the Goals